Análisis estadístico de los tipos de sombreado y su efecto en el rendimiento y protección del cultivo de piña – poroto – 2016 - Torres Rodríguez, Jonathan (2017)
The objective of the present investigation is to perform the statistical analysis of an experiment presented as a randomized complete block design to compare the expected effect of five types of shading for pineapple cultivation in the Santa Catalina valley of the Poroto district; From each experimental plot the fruits of five plants were extracted and the study variables were examined: fruit length, fruit diameter, fruit weight and the number of pineapples burned per plot. The methodology applied to the data that were collected in the project "Generation of Productive Technology in Red Pineapple Trujillana to the Producers of the Santa Catalina Valley - Poroto" PIC-07: 330313207 "of the Laboratory of Soils in the Faculty of Agricultural Sciences of the University National of Trujillo._x000D_ In merit to the indicated thing, as is common in the cases of experiments in agriculture, horticulture and forestry these form rectangular matrices in their designs; For this case it is corroborated that the location of the plots conform to a R.C.B.D. In a restricted manner (efficient row and column design) with a randomization in both the blocks and columns being a rectangle of 5 - 4 repetitions, as a result it was observed that the types of shading for fruit cultivation have no influence or effect on their Length, weight and diameter, variables used to measure the yield of pineapple, and to the application of the nonparametric test (Homogeneity Test) in the number of pineapple burns per plot could be obtained that if there is a difference between the Applied treatments, and in turn it was shown that two of the applied treatments are those that protect the fruit considerably, a result obtained through a multiple comparison of hypothesis tests of sample proportions